Decisions for others become less impulsive the further away they are on the family tree - Ziegler, Fenja V.; Tunney, Richard J. (Public Library of Science, 2012)
People tend to prefer a smaller immediate reward to a larger but delayed reward. Although this discounting of future rewards is often associated with impulsivity, it is not necessarily irrational. Instead it has been suggested that it reflects the decision maker’s greater interest in the ‘me now’ than the ‘me in 10 years’, such that the concern for our future self is about the same as for someone else who is close to us. Methodology/Principal Findings: To investigate this we used a delay-discounting task to compare discount functions for choices that people would make for themselves against decisions that they think that other people should make, e.g. to accept $500 now or $1000 next week. The psychological distance of the hypothetical beneficiaries was manipulated in terms of the genetic coefficient of relatedness ranging from zero (e.g. a stranger, or unrelated close friend), .125 (e.g. a cousin), .25 (e.g. a nephew or niece), to .5 (parent or sibling). Conclusions/Significance: The observed discount functions were steeper (i.e. more impulsive) for choices in which the decision-maker was the beneficiary than for all other beneficiaries. Impulsiveness of decisions declined systematically with the distance of the beneficiary from the decision-maker. The data are discussed with reference to the implusivity and interpersonal empathy gaps in decision-making.